Noninvasive Electromagnetic Detection of Bladder Cancer. (16th January 2014) - Cormio, Luigi; Vedruccio, Clarbruno; Leucci, Giorgio; Massenio, Paolo; Di Fino, Giuseppe; Cavaliere, Vincenzo; Carrieri, Giuseppe
Abstract : Objectives . Normal and neoplastic human tissues have different electromagnetic properties. This study aimed to determine the diagnostic accuracy of noninvasive electromagnetic detection of bladder cancer (BC) by the tissue-resonance interaction method (TRIM-prob). Patients and Methods. Consecutive patients were referred for cystoscopy because of (i) microscopic or gross hematuria and/or irritative voiding symptoms and (ii) bladder ultrasounds and urinary cytology findings negative or just suspicious of malignancy. Patients were first submitted to TRIM-prob bladder scanning by a single investigator and then to cystoscopy by another investigator blind to TRIM-prob data. Results . In 125 evaluated patients cystoscopy was positive for BC in 47 and negative in the remaining 78; conversely, TRIM-prob bladder scanning was positive for BC in 53 and negative in 72. In particular, TRIM-prob scanning yielded 7 false positives and only one false negative; therefore, its overall sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy were 97.9%, 89.9%, 86.8%, 98.6%, and 93.6%, respectively. Conclusions . TRIM-prob bladder scanning was a simple and quite accurate method for non-invasive electromagnetic detection of BC. If the elevated positive and negative predictive values will be replicated in further well-designed studies, it could be used to screen asymptomatic patients at high risk of BC.